The Influence of Resilience and Nurse Motivation on Job Stress in Hospital: A Systematic Review - Maria Silveira De Jesus; Mira Triharini; Nuzul Qur’aniati (Indonesian Journal of Global Health Research, 2025)
This study aims to analyse the influences of resiliences and nurse motivation on job stress. This study was conducted because nursing is a profession that is often faced with stressful and environments work situations, and nurses also often involve interactions with patients who are suffering or dying, which can affect their mental health. Without resilience and motivation, they may feel overwhelmed, anxious, or even experience burnout (emotional exhaustion). Method: The method used was a systematic review sourced from journals searched through the Scopus, Science Direct, and Pubmed databases published in less than the last 5 years (2019-2024) This systematic review follows the PRISMA. by using four databases in journal searches. This research uses the PEOS framework to determine the criteria. Based on the results of the literature search that has been examined, and in accordance with the eligibility criteria, 10 articles were obtained that can be used in this systematic review. Results Based of the 10 research journals that were analyzed, the results were varied, including 2 journals showing that work fatigue was a cause of moderate to severe stress in nurses and was one of the causes of nurses thinking about leaving their jobs as nurses. Meanwhile, 4 other articles discuss resilience and work stress levels of nurses, where the results show a significant relationship between resilience and stress levels. Based on the results of the review carried out, it can be concluded that nurses who have a good level of resilience will easily adapt and can control stress caused by work fatigue and burnout. Of the 10 research journals that were analyzed, the results were varied, including 2 journals showing that work fatigue was a cause of moderate to severe stress in nurses and was one of the causes of nurses thinking about leaving their jobs as nurses. Meanwhile, 4 other articles discuss resilience and work stress levels of nurses, where the results show a significant relationship between resilience and stress levels. Conclusion The purpose of this research is to assess how resilience being important to mannage stress and burnout for a health workers especially nurses.